Características reprodutivas de rainhas africanizadas (Apis mellifera) silvetres no litoral de Alagoas - Lima, Erica Gomes de (2013)
This study aimed at obtaining basic information about the reproductive quality of feral Africanized honeybee queens (Apis mellifera) from the coastal region of Alagoas State. The colonies’ nesting characteristics (e.g.: Size of the nest cavity, height, orientation, number and color of combs) were also studied. Thirty swarms were assessed. All combs were mapped during the capture using Al-Tikrity´s methodology. The queens were found and taken to the laboratory in order to take morphometric measurements (weight, length) and to dissect their spermateca and ovaries for sperm and ovarioles counting. The great majority of swarms were found in cavities. A preference for cavities in a tree called red cupiúba (Goupia glabra) was observed. The feral honeybee queens captured in the present work were relatively small in comparison to other studies. The average weight obtained was of 198.9 mg. The number of ovarioles of the studied queens was in accordance with numbers recorded for this species. The average number counted on right ovaries was 144. Nevertheless, the queen’s fecundity (number of spermatozoa in the spermatecas) was far from optimal. The mean number of spermatozoa obtained from the studied queens was 1,5 x 106. No relationship was found between queen’s morphological characteristics and their reproductive characteristics.